Effect of magnetized water on the germination of Cotton seeds (Gossypium hirsutum L.) under different conditions of saline stress - Saba Ali Alzubaidi (Kufa Journal for Agricultural Sciences)
A laboratory experiment was designed with two factors by using completely randomized design (CRD) with three replicates to determine the effect of saline stress and magnetized water on the germination of cotton seeds. The first factor included salt concentrations of (0, 3, 6, 9 ds.m-1), and the second factor included magnetized water with intensity of 1000 gauss and distilled water (control treatment). The seeds were planted on blotting paper and experimental units were placed inside germinator at temperature in the range of 20-30ºC for 12 days[9]. The results showed that the use of magnetized water caused a significant increase in the studied traits (germination percentage, germination speed, radicle length, plumule length, and the weight of seedlings)as compared to non-magnetized water. In addition, saline irrigation water has significantly reduced all studied traits as compared to the use of distilled water (0 ds.m-1). There was also a significant interaction between concentrations of salinity and magnetized water, in which magnetism has improved the properties of studied trails under saline conditions  as compared to non-magnetized water.